2013
DOI: 10.1002/pen.23754
|View full text |Cite
|
Sign up to set email alerts
|

Pendant crosslinked poly(aryl ether sulfone) copolymers sulfonated on backbone for proton exchange membranes

Abstract: A series of sulfonated poly(aryl ether sulfone) copolymers containing phenyl pendant groups with sulfonic acid groups on the backbone were synthesized through condensation polymerization. The degree of sulfonation (DS) of the copolymers was controlled by changing the feed ratios of sulfonated to unsulfonated monomers. Post‐crosslink reactions are carried out with 4,4′‐thiodibenzoic acid (TDA) as a crosslinker and the carboxylic acid groups in TDA can undergo Friedel–Craft acylation with the phenyls pendent rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The pendant carboxylic or sulphonic acid groups present on the main backbone of the polymer chain enhance the proton conductivity of the membrane [12][13][14]. These pendant groups have also been utilized further for crosslinking to improve the dimensional stability and various fuel-cell-related properties of the pristine membrane [15,16]. Studies of poly(vinyl alcohol) [PVA]-based membranes have shown that they possess excellent film-forming properties, besides showing high chemical resistance and thermo-stability [17].…”
Section: Introductionmentioning
confidence: 99%
“…The pendant carboxylic or sulphonic acid groups present on the main backbone of the polymer chain enhance the proton conductivity of the membrane [12][13][14]. These pendant groups have also been utilized further for crosslinking to improve the dimensional stability and various fuel-cell-related properties of the pristine membrane [15,16]. Studies of poly(vinyl alcohol) [PVA]-based membranes have shown that they possess excellent film-forming properties, besides showing high chemical resistance and thermo-stability [17].…”
Section: Introductionmentioning
confidence: 99%
“…These include poly(arylene ether ketone)s, poly(arylene ether sulfone)s (PAESs) [6][7][8][9][10][11], poly(arylene ether nitrile)s [12,13], poly(phthalazinone arylene ether)s [14,15], polyimides [16][17][18]. Extensive work has also been carried out on polybenzimidazole based membranes which represents the class of PEMs having acid-base interactions and are suitable for high temperature operating fuel cell applications.…”
Section: Introductionmentioning
confidence: 98%
“…Until now, several different polymers have been used for membranes in ED applications, such as, polystyrene, [ 12,13 ] polyether imide, [ 14,15 ] polyether ether ketone, [ 16,17 ] polyether benzimidazole, [ 18,19 ] and polyarylene ether. [ 20‐22 ] The sulfonation of these polymers leads to improved membrane properties, that is, better wettability, better permselectivity, higher water flux, higher ionic conductivity, and better ionic exchange capacity. Those improved properties make these sulfonated polymers good candidates for IEM commercial materials.…”
Section: Introductionmentioning
confidence: 99%